Factors associated with dream enacting behaviors among US farmers. (December 2018) - Shrestha, Srishti; Kamel, Freya; Umbach, David M.; Fan, Zheng; Beane Freeman, Laura E.; Koutros, Stella; Alavanja, Michael; Blair, Aaron; Sandler, Dale P.; Chen, Honglei
Abstract: Introduction: Dream enacting behavior (DEB) during REM sleep is a characteristic feature of REM sleep behavior disorder (RBD), the most specific prodromal symptom for Parkinson's disease (PD) and related synucleinopathies. Methods: We screened for DEB among 20, 591 male farmers in 2013–2015 using a validated question, and examined its association with pesticide uses and other potential risk factors reported about twenty years ago in 1993–1997. We reported odds ratios (OR) and 95% confidence intervals (CI) from multivariable logistic regression models. Results: A total of 1623 (7.9%) farmers reported having had DEB. Farmers with DEB were more likely to report other nonmotor and motor symptoms of PD with age-adjusted ORs ranging from 1.9 to 3.0. DEB prevalence varied little by age, but was significantly associated with current smoking (adjusted OR: 1.4, 95%CI: 1.2, 1.6), daily alcohol drinking (OR: 1.4, 95%CI: 1.1, 1.6), a history of head injury (OR: 1.3, 95%CI: 1.2, 1.5), and being married (OR: 1.4, 95%CI: 1.1, 1.7). We identified significant associations for several pesticides, especially cyclodiene organochlorines and pyrethroids, with adjusted ORs ranging from 1.2 to 1.5. The results were similar after excluding PD cases or when farmers with at least three DEB episodes in life were considered as DEB cases. Conclusions: This study suggests that DEB are not rare among male farmers. Findings on potential risk factors for DEB are intriguing, and given the close link between RBD and PD, these associations should be further investigated. Highlights: In a survey of 20, 591 male farmers, 7.9% reported dream enacting behaviors (DEB). Active smokers and daily alcohol drinkers were more likely to report DEB. DEB was more common among those with a history of head injury. Some pesticides, specifically organochlorines, were linked to DEB.